Whether to Waive Parental Permission in HIV Prevention Research Among Adolescents: Ethical and Legal Considerations. Issue 1 (2020) - Bauman, Laurie J.; Mellins, Claude Ann; Klitzman, Robert
Abstract : Critical ethical questions arise concerning whether studies among adolescents of new behavioral and biomedical HIV preventive interventions such as Pre-Exposure Prophylaxis (PrEP) should obtain parental permission. This paper examines the relevant regulations and ethical guidance concerning waivers of parental permission, and arguments for and against such waivers. Opponents of such waivers may argue that adolescent decision-making is "too immature" and that parents always have rights to decide how to protect their children. Yet requiring parental permission may put adolescents at risk, and/or limit adolescent participation, jeopardizing study findings' validity. This paper presents recommendations on when researchers and Institutional Review Boards (IRB) should waive parental permission, and what special protections should be adopted for adolescents who consent for themselves, e.g., assuring adolescent privacy and confidentiality, screening for capacity to consent, and identifying adolescents who are at elevated risk from study participation. We also present a series of specific areas for future research to design tools to help make these assessments, and to inform researcher and IRB decisions. These recommendations can help ensure that research is conducted that can aid adolescents at risk for HIV, while minimizing risks and protecting these individuals' rights as much as possible.